2011
DOI: 10.1038/pcan.2011.33
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional and post-transcriptional regulation of Sprouty1, a receptor tyrosine kinase inhibitor in prostate cancer

Abstract: Sprouty1 (Spry1) is a negative regulator of fibroblast growth factor signaling with a potential tumor suppressor function in prostate cancer (PCa). Spry1 is downregulated in human PCa, and Spry1 expression can markedly inhibit PCa proliferation in vitro. We have reported DNA methylation as a mechanism for controlling Spry1 expression. However, promoter methylation does not seem to explain gene silencing in all PCa cases studied to suggest other mechanisms of gene inactivation, such as alterations in trans-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…It has previously been reported that in prostate cancer, SPRY1 is regulated by miR-21 [Darimipourain et al, 2011] a microRNA that is regulated by androgens and associated with prostate cancer or disease progression [Ribas et al, 2009]. Using Target Scan (http://www.targetscan.org/), miR-21binding sites in the 3’UTR were found in SPRY1 and in JAG1 (Supplement Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that in prostate cancer, SPRY1 is regulated by miR-21 [Darimipourain et al, 2011] a microRNA that is regulated by androgens and associated with prostate cancer or disease progression [Ribas et al, 2009]. Using Target Scan (http://www.targetscan.org/), miR-21binding sites in the 3’UTR were found in SPRY1 and in JAG1 (Supplement Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PTEN loss-of-function, which is one of the most common and important oncogenic changes in human prostate cancer (2, 3), can be accompanied by silencing of Sprouty genes potentially as a result of multiple mechanisms including hypermethylation (27,34) and aberrant microRNA expression (35). Because we have shown here that Sprouty genes are modulators of tumorigenesis caused by loss of Pten function, future studies aimed at obtaining a deeper understanding of the molecular consequences of Sprouty loss-of-function should provide insight into the rewiring of key oncogenic signaling pathways that occurs in the cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of SPRY1 in LNCaP and PC-3 cells significantly inhibits cell growth (Kwabi-Addo et al, 2004). Increased methylation of the SPRY1 promoter and miR-21 mediated repression are in part responsible for abnormal SPRY1 silencing that occurs in prostate cancer (Kwabi-Addo et al, 2009;Darimipourain et al, 2011). More recently, it was confirmed in vivo that Spry1 and Spry2 function together to inhibit prostate cancer progression (Schutzman and Martin, 2012).…”
Section: Prostate Cancermentioning
confidence: 96%